Reverse culture shock among Saudi students returning from the US to to thier homeland - Alkhalaf, Khulud; Al-Krenawi, Alean; Elbedour, Salman (Journal of International Students, 2024)
This study examines reverse acculturative stress among Saudi students returning to their home country after studying in the USA. A study on Saudi students is particularly important due to scant empirical attention on Middle Eastern students. Given the population size of returning Saudi students, it is worth analyzing their adaptation to their home country, especially as the KSA has renewed its efforts at “saudification of the workforce,” a goal that relies on a highly educated population. 96 university students participated in the study. Because of the gap in values between Saudi Arabia and the USA, the study hypothesized that Saudi returnees who reported higher levels of reverse culture shock would report lower life satisfaction and quality of life. Additionally, the study posited that students’ identification with their Saudi heritage would correlate negatively with reverse culture shock. A novel tripartite intervention model is proposed to reduce reverse culture shock.